AN EXPLORATORY STUDY ON THE YOUTH UNEMPLOYMENT IN NORTH-EAST INDIA - Purna Laxmi Jamatia; Dr. R. Gurumoorthy (CV. Radja Publika, 2023)
While the population is growing quickly and education is improving, work prospects remain limited due to economic underdevelopment, perpetuating the problem of youth and educated unemployment. Most states in the Northeast have worse educated and youth unemployment than the rest of the country. Most of the Northeastern states, as well as the rest of the country, saw a higher rate of youth unemployment in urban regions than in rural ones, and among women than among men. Educated unemployment is common in both rural and urban areas, but it disproportionately affects women in many Northeastern states.